Survey on Research Advancements in WiMedia MAC Protocol - Umadevi, K. S.; Thangavelu, Arunkumar (International Journal of Engineering and Technology Innovation, 2017)
WiMedia Alliance is an entity of personal area network occupying the large scale of real time applications with its attractive features like high data rate with low energy consumption. WiMedia Medium Access Control protocol is equipped in such a way that they can communicate with its counterpart to form a network. This enables advances in technology and availability to facilitate the extensive deployment of WiMedia network. But the overall performance of WiMedia network is limited due to factors like coverage distance, Interference, Mobility, Energy Consumption etc. So in this paper, we present the comprehensive survey of recent advancements in WiMedia Mac to provide a platform for a better consideration of WiMedia Medium Access Control research status to potential researchers and highlight the combined effect of WiMedia and other technologies.